A founding-team model of creating a venture's culture - Shepherd, Dean A.; Breugst, Nicola; Patzelt, Holger (Journal of Business Venturing, 2023)
As many new ventures are started by founding teams, it is these founding teams that likely engage in creating their venture's culture. We draw on theories of cultural dynamics and the literature on team cognitive diversity to investigate the creation of a new venture's culture. Specifically, we theorize how a founding team's cognitive diversity impacts the team's production of cultural information and the transmission of that information throughout the venture. Cognitive diversity directly influences the founding team's production of cultural information by shaping the diversity of the information set and the speed of its production. Moreover, cognitive diversity can give rise to faultlines within the venture, impacting how venture members interpret cultural information. Importantly, our model suggests a complex interplay between the production and interpretation of cultural information. Understanding culture creation in new ventures is important because a new venture's culture shapes its legitimacy and thus its access to stakeholder resources for venture emergence.